Long term hypoxia during gestation alters perirenal adipose tissue gene expression in the lamb - Myers, Dean A. (Adipocyte, 2020)
We previously reported that following long-term hypoxia (LTH), the ovine foetus exhibits enhanced expression of brown/beige adipose genes. This study was designed to determine if these changes are preserved after birth. Pregnant ewes were divided among three groups, 1) Control, sea level, 2) LTH, high altitude (3,820 m, LTH-HA) from ~ day 40 of gestation through ~14 days post-delivery and 3) LTH from ⁓ day 40 through day 137 of gestation then returned to the laboratory where atory reduced maternal PO(2) was maintained by nitrogen infusion. Following delivery, lambs remained at sea level (LTH-SL). Perirenal adipose tissue was collected at ~day 14, and qRT-PCR was used to quantify mRNA. Uncoupling protein 1 (UCP-1), PPAR gamma coactivator 1 (PGC1α), and deiodinase-2 (DIO2) mRNA levels were significantly lower in both LTH groups while PR domain containing 16 (PRDM16) levels did not differ. Peroxisome proliferator-activated receptor (PPARγ) was maintained in the LTH-HA group and significantly increased in the LTH-SL group, compared to control. Unlike our previous LTH foetal studies, the brown/beige fat phenotype was rapidly lost by day 14 postpartum compared to control, while PPARγ was maintained. This loss of the brown fat phenotype may promote obesity due to decreased energy expenditure, favouring fat deposition.